2009
DOI: 10.1890/08-0729.1
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of Corallorhiza odontorhiza reflect variations in climate and ectomycorrhizae

Abstract: The abundance and reproductive activity of orchids have been linked to variations in weather conditions, but few investigators have examined the relationships between orchid flowering dynamics and the distribution and abundance of mycorrhizal fungi. We quantified the abundance of flowering individuals of Corallorhiza odontorhiza, a mycoheterotrophic orchid, over a 14-year period and mapped the distribution of individuals in six of the 14 years. For two seasons, we conducted intensive and extensive studies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 75 publications
2
76
0
Order By: Relevance
“…These fungi have previously been shown to associate with orchids that typically occur in forests. For example, the major fungi associating with the mycoheterotrophic Corallorhiza odonthorhiza were Tomentella fungi34. In the forest orchids Cephalanthera damasonium and C. longifolia several members of the Thelephoraceae, including Tomentella and Pseudotomentella , were found in germinating seeds35 (Bidartondo & Read 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These fungi have previously been shown to associate with orchids that typically occur in forests. For example, the major fungi associating with the mycoheterotrophic Corallorhiza odonthorhiza were Tomentella fungi34. In the forest orchids Cephalanthera damasonium and C. longifolia several members of the Thelephoraceae, including Tomentella and Pseudotomentella , were found in germinating seeds35 (Bidartondo & Read 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The fungi within each clade were grouped further into operational taxonomic units (OTUs) defined by 95% sequence similarity, as determined by the furthest-neighbor algorithm in DOTUR (Schloss and Handelsman 2005). It is possible that the use of ITS sequence similarity cutoffs to define OTUs representing putative species may underestimate fungal diversity; however, this methodology is widely used in mycorrhizal research (Nilsson et al 2008;McCormick et al 2009;Lievens et al 2010), because of the difficulties associated with obtaining multigene phylogenetic data from environmental samples. Note that for a subset of orchid taxa, we confirmed that identified fungi were mycorrhizal and not other associated fungi by field seed-germination experiments described below.…”
Section: Identification Of Pollinators and Attachmentmentioning
confidence: 99%
“…Numerous research aimed to recognize variables affecting the distribution and abundance of various orchids (e.g. Bergman et al 2006, O'Malley 2009, McCormick et al 2009, Bunch et al 2013, García-González et al 2016 indicating the importance of geography, soil chemistry, phorophyte specificity, presence of mycorrhizal fungi and pollinators, landscape heterogeneity, as well as landuse history. However, climate is the most important component of fundamental niche which is formed as a result of evolution.…”
Section: Glacial Refugia and Future Potential Range Changes-mentioning
confidence: 99%